Contribution of tourism to sustainable rural development in Sri Lanka - Aslam, M.S.M. (2014)
Development is the critically analysed phenomenon in the contemporary world and disadvantaged development or dilemmas in rural development are vastly observed issues. Neo-liberalization and modernization theories pushed many countries to adopt tourism as a developmental tool to overcome the economic challenges. Today, tourism is one of the largest industries with reference to the volume of the business and employment generation globally. However, uncontrollable negative impacts surpass the positive impacts and cause rapid degradation on socio-cultural and environmental resources. At present, ensuring sustainability is a primary criterion for any tourism developmental interventions. Tourism also has been recognized as a driving force of sustainable development while the needs of sustainable tourism development have been well documented. Conceptualization of sustainability claims a shift from conventional mass tourism to alternative tourism. Inability of sustainable practices in urban environments pushes the alternative tourism into rural areas. Although alternative tourism envisages sustainability, rural areas encounter many issues and problems in ensuring authentic and consistent sustainable rural tourism development. Critical review of wide array of published and unpublished documents either in the forms of printed or electronic versions persuades an empirical study in socially constructed world. This illuminates the multiple realities on unsuccessful sustainable rural tourism development. Review of overall tourism developmental phenomena generally and contemporary status of rural Sri Lanka particularly justify the appropriateness of the case selection. In depth interviews, focus group discussions, direct observations, documental reviews, artefacts and consistent field notes bring forth the naturalistic interpretations from the social world of rural Sri Lanka. Rigor reporting and understandable interpretation of the natural settings have been determined by appropriate designing, data collection, analysis, interpretation and verification of the methodology. Empirical findings are categorised into two clusters. First cluster elucidates unfocused and incompatible rural tourism development in rural Sri Lanka. This is as a result of poor rural community capacity and participation, erratic intervention and lack of coordination and collaboration in different levels of authorities and limited role of Non Governmental Organizations (NGOs). Second cluster reveals insufficient and inappropriate application of strategic tools in sustainable rural tourism development of Sri Lanka. This encompasses inadequate capacity building and inconsistent role of authority and NGOs in it, noncompliance product designing and development, weak policy setting and implementation, instability and unavailability of investment and incentives, diluted marketing approach along with limited networking and accreditation. The empirical findings are funnelled into six major themes related to participation and intervention of community, authority and NGOs and incorporation of strategic tools. The study surfaces a number of theoretical and managerial implications. And the comprehensive process of sustainable rural tourism development is reframed into a strategic window. This study envisages a number of recommendations for developers, policymakers and communities to visualize sustainable rural tourism development, while suggesting the future research agenda.